Identification of quantitative trait loci for resistance against soybean sudden death syndrome caused by Fusarium tucumaniae - Yamanaka, Naoki; Fuentes, Francisco Horacio; Gilli, Javier Ramon; Watanabe, Satoshi; Harada, Kyuya; Ban, Tomohiro; Abdelnoor, Ricardo Vilela; Nepomuceno, Alexandre Lima; Homma, Yoshihisa (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to identify genomic regions that underlie resistance to Fusarium tucumaniae sp. nov., the causing agent of sudden death syndrome (SDS) in soybean in South America, using a population with a genetic background different from that previously reported for Fusarium virguliforme sp. nov. (F. solani f. sp. glycines), also responsible for SDS in soybean. Although major genes and quantitative trait loci (QTL) for SDS resistance have been identified, little is known about the same disease caused by Fusarium tucumaniae sp. nov., in South America. To identify genetic factors related to resistance to F. tucumaniae and DNA markers associated with them, a QTL analysis was performed using recombinant inbred lines. The map locations of the four loci, here identified, differed from those SDS resistance QTL previously described. It was screened a residual heterozygous line (RHL), which was heterozygous around the most effective QTL, RSDS1, and homozygous for the other genomic regions. The genetic effect of RSDS1 was confirmed using near-isogenic lines (NIL) derived from the RHL. The line which was homozygous for the Misuzudaizu genotype showed resistance levels comparable with that of the line homozygous for the Moshidou Gong 503 genotype.